Effect of rice straw ash on soil properties and yield of cucumber - Muazu Dantala, Zakari; Babangida, Ibrahim; Nasid, Nuraddeen Mukhtar; Jafar Shanonoa, Nura; Muntaqqa, Ibrahim; Tijjani, Usman; Abubakar, Ahmad (University of El-Oued, 2019)
Many farmers in Nigeria are paying close attention to using Rice Straw Ash (RSA) as a soil fertility enhancement additive. The short and long-term effects of applying this ash to the soil quality were not adequately investigated, however. This research was conducted at the Departmental Farm of Agricultural and Environmental Engineering, Bayero University, Kano to access the impact of RSA on the soil’s physiochemical properties and on cucumber yield. Twelve (12) experimental plots were treated with different amounts of RSA (0 Kg, 1 Kg, 2 Kg and 3 Kg) to assess the intensity effect of the treatment on both soil physiochemicals and crop yield. For each experimental plot, soil properties (moisture content, porosity, bulk density, electrical conductivity, organic matter, pH and sodium concentration, nitrogen, phosphorus, potassium, calcium and magnesium) were measured and analyzed before and after the experiment. The results showed that the application of ash increased moisture content, bulk density, porosity, electrical conductivity, organic matter and sodium concentration while reducing the pH, nitrogen, phosphorus, potassium, calcium and magnesium levels. The mean yield in 0 Kg RSA (21,84tons / ha) was found to be the highest. There was a drop in the yield (13.08-14.14tons / ha) of crop in the plots treated with RSA. The research concluded that continued use of RSA could lead to a reduction in crop yield as the EC level was found to be rising. It is on this basis that farmers are advised to avoid the use of RSA as an additive for soil fertility enhancement and other means should therefore be used.
Article in Algerian Journal of Engineering and Technology. university of el oued
Keywords: Rice; Straw; Ash; Cucumber Yield.